(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
As a result of the study, it was established that in the vicinity of Osh there are 5 species of mouse-like rodents, among which house mice (Mus musculus) dominate. As a result of the autopsy, 797 copies. small rodents caught in Osh and its environs, 888 specimens were found. nematodes belonging to 10 species, 3 genera, 3 families and suborders. In terms of the number of individuals in all biotopes, Suphaciaobvelata dominates - 261 specimens, Syphacia montana - 253 specimens.